A Narrative Review Examining the Utility of Interpersonal Synchrony for the Caregiver-Care Recipient Relationship in Alzheimer’s Disease and Related Dementias - Gifford, Angela; Marmelat, Vivien; Beadle, Janelle N. (Frontiers in Psychology, 2021)
The stressful nature of caring for an older adult with a chronic disease, such as Alzheimer’s disease (AD), can create barriers between the caregiver-care recipient, as they try to navigate their continuously changing social relationship. Interpersonal synchrony (i.e., matching or similarity of movement, emotions, hormones, or brain activity), is an innovative approach that could help to sustain caregiving relationship dynamics by promoting feelings of connection and empathy through shared behavior and experiences. This review investigates the current literature on interpersonal synchrony from an interdisciplinary perspective by examining interpersonal synchrony through psychological, neural, and hormonal measures across the adult lifespan. We then present a case for examining the degree to which interpersonal synchrony can be used to facilitate affiliation and well-being in the caregiver-care recipient relationship. We find that there is significant evidence in healthy adult populations that interpersonal synchrony can support affiliative feelings, prosocial behavior, and well-being. Characterizing the psychological, neural, and hormonal mechanisms of interpersonal synchrony is a first step towards laying the groundwork for the development of tools to support relational closeness and empathy in the caregiving context. Finally, we explore the strengths and limitations of using interpersonal synchrony to support relational well-being, and discuss possible avenues for future research.